Reduced Resident Work Hours in Urology: The History and Impact of Duty Hour Restrictions. Issue 6 (November 2016) - Kirby, Will E.; Carson, Culley C.
Abstract : Introduction: : The ACGME first mandated duty hour restrictions for resident physicians in 2003, setting a limit of 80 hours per week. While the goals of this and later reforms were to improve patient care and safety, the outcomes have been mixed. In this review we report on the history of duty hour regulations and how these changes have impacted resident and patient outcomes. Methods: : A literature search was performed, and articles discussing surgical training, resident duty hours, resident wellness and patient outcomes were reviewed. Results: : After implementation of duty hour restrictions in 2003, the Harvard Work Hours Health and Safety Group published 3 hallmark studies that suggested duty hour restrictions were associated with improved outcomes. A recently published systematic review reported mixed results from the growing body of research. While 71% of the reviewed studies reported improvement in resident wellness, only 4% illustrated an improvement in resident education, 19% reported improved patient safety outcomes and 13% demonstrated improved patient morbidity. Conclusions: : Resident duty hour restrictions were based on a body of evidence illustrating that fatigue and sleeplessness negatively impact decision making, resident wellness and patient care. While initial outcomes suggested that these regulations resulted in better resident and patient outcomes, more recent evidence suggests otherwise. There is very little urology specific evidence addressing these matters.